The practice of key essential nutrition actions among pregnant women in southwest Ethiopia: implications for optimal pregnancy outcomes - Shamil Mudasir; Ebrahim Muktar; Abdu Oumer (BMC Pregnancy and Childbirth, 2024)
Abstract Background Nutrition during pregnancy is a major determinant of human health and child development, and the role of promoting essential nutrition actions (ENA) is of a paramount importance for the health of the mother and newborn. However, the practice of ENA could be hampered by many factors, which need to be understood for tailored actions. This study assessed the practice of key ENAs and associated factors among pregnant mothers in southwest Ethiopia. Method A community-based cross-sectional study was employed among 373 pregnant mothers. A simple random sampling method was used to select the study participants. The data was entered into EpiData Manager and exported to SPSS version 21 for analysis. A bivariable logistic regression was conducted to explore the association between independent variables and the outcome variable. Variables with p-values less than 0.25 during bivariable analysis were entered into a multivariable logistic regression model. Level of statistical significance was declared at a p-value below 0.05. The crude and adjusted odds ratios, along with the 95% CI, were estimated to measure the strength of the association between the dependent variables and independent variables. Result In this study, 373 pregnant mothers have participated, with a response rate of 97%. A total of 275 (73.7%; 95% CI: 68.9–78.0) women practiced key essential nutrition actions at optimal level. Monthly household income of 2500 ETB (AOR = 0.45, 95% CI: 0.23, 0.89), rural residence (AOR = 2.31, 95% CI: 1.25, 4.4), and poor knowledge of key ENA messages (AOR = 3.36, 95% CI: 1.81, 6.26) were factors that were significantly associated with poor practice of key ENA messages. Conclusions The practice of key ENA messages was poor and closely linked to household income, residence, and knowledge of pregnant women’s on ENA key messages. Therefore, nutritional intervention with a focus on intensified nutritional counseling is needed for better adoption of key ENA practices.